Epstein‐Barr virus‐positive gastric cancer involves enhancer activation through activating transcription factor 3. Issue 5 (20th March 2020) - Asakawa, Yuta; Okabe, Atsushi; Fukuyo, Masaki; Li, Wenzhe; Ikeda, Eriko; Mano, Yasunobu; Funata, Sayaka; Namba, Hiroe; Fujii, Takahiro; Kita, Kazuko; Matsusaka, Keisuke; Kaneda, Atsushi
Abstract: Epstein‐Barr virus (EBV) is associated with particular forms of gastric cancer (GC). We previously showed that EBV infection into gastric epithelial cells induced aberrant DNA hypermethylation in promoter regions and silencing of tumor suppressor genes. We here undertook integrated analyses of transcriptome and epigenome alteration during EBV infection in gastric cells, to investigate activation of enhancer regions and related transcription factors (TFs) that could contribute to tumorigenesis. Formaldehyde‐assisted isolation of regulatory elements (FAIRE) sequencing (‐seq) data revealed 19 992 open chromatin regions in putative H3K4me1 + H3K4me3 − enhancers in EBV‐infected MKN7 cells (MKN7_EB), with 10 260 regions showing increase of H3K27ac. Motif analysis showed candidate TFs, eg activating transcription factor 3 (ATF3), to possibly bind to these activated enhancers. ATF3 was considerably upregulated in MKN7_EB due to EBV factors including EBV‐determined nuclear antigen 1 (EBNA1), EBV‐encoded RNA 1, and latent membrane protein 2A. Expression of mutant EBNA1 decreased copy number of the EBV genome, resulting in relative downregulation of ATF3 expression. Epstein‐Barr virus was also infected into normal gastric epithelial cells, GES1, confirming upregulation of ATF3 . Chromatin immunoprecipitation‐seq analysis on ATF3 binding sites and RNA‐seq analysis on ATF3 knocked‐down MKN7_EB revealed 96 genes targeted by ATF3‐activating enhancers, which are related with cancer hallmarks, eg evading growth suppressors. These 96 ATF3 target genes were significantly upregulated in MKN7_EB compared with MKN7 and significantly downregulated when ATF3 was knocked down in EBV‐positive GC cells SNU719 and NCC24. Knockdown of ATF3 in EBV‐infected MKN7, SNU719, and NCC24 cells all led to significant decrease of cellular growth through an increase of apoptotic cells. These indicate that enhancer activation though ATF3 might contribute to tumorigenesis of EBV‐positive GC. Abstract : Through integrated analyses on alterations of transcriptome, histone modification, and open chromatin status during Epstein‐Barr virus (EBV) infection in gastric cells, we here identified activating transcription factor 3 (ATF3) as a critical transcriptional activator with involvement in enhancer activation. We undertook screening of putative transcription factors binding to activated enhancer regions and identified ATF3 as a transcription factor that is upregulated by EBV infection and induces aberrant enhancer activation. Effect of ATF3 expression on cellular proliferation was confirmed, suggesting a tumorigenic role of aberrant enhancer activation by ATF3 upregulation, which could help our understanding of the tumorigenic mechanisms in this particular subtype of gastric cancer.